O papel do coordenador pedagógico na formação crítica de professores: contribuições e desafios - Orfão, Elizabeth Tagliatella (2018)
This paper aims at analyzing the contribution of the continuous education process developed by the Professional Training Center of Education (Centro de Capacitação de Profissionais da Educação), in 2017; with pedagogical coordinators who work in elementary schools in São Caetano do Sul. The study is founded on a critical, collaborative and reflexive perspective that, in creating collective spaces of exchanges and discussions, seeks to investigate the lived reality and its possibilities of reconstruction. With this focus, the professionals involved in the research are expected to discuss and seek answers to the day-to-day challenges of school through shared responsibility, commitment and improvement of the group. For this purpose, firstly a survey on the formative needs of the subjects involved was made and, later, a formative proposal in which the participants analyzed and discussed their challenges towards teacher education was elaborated. The Critical Collaborative Research (PCCol) (MAGALHÃES, 2004) methodologically bases this study once it discusses how the research course itself constitutes the possibility for all participants to learn in a more collaborative and interventional way. Data were produced by use of: 1. description of the activity context; 2. written evaluations; 3. pictures; and 4. audio recording, and analyzed with the support of the theoretical frame and the actions of critical reflection - describe, inform, confront and reconstruct (SMYTH, 1992). The results have pointed to the importance of creating spaces that provoke strangeness and continuous collective exchanges to expand the possibilities of intervention. This research can offer contributions in the elaboration of formative activities that may develop new ways of acting and thinking in the search for shared meanings to face the challenges that compose this process